Reabilitação estética do sorriso por meio do sistema cerâmico dissilicato de lítio: relato de caso - Pedrazzi, Hamilton; Santos , Carla Raquel dos; Takeuchi, Cristina Yoshie Garcia [UNESP]; Andrade, Marcelo Ferrarezi de [UNESP] (My University, 2014)
The reestablishment of a harmonious smile through dental ceramics, when properly conducted and with specific indications, can achieve extremely predictable results. For aesthetic and functional rehabilitation, many ceramic materials can be used such as zirconia, leucite, alumina, feldspar, and lithium disilicate. Among these materials the lithium disilicate stands out due to the following characteristics: its resistance to wear, to chemical attack, high temperatures and oxidation; low electrical conductivity; near zero thermal expansion; good optical properties and biocompatibility with periodontal; excellent esthetics; color stability and reinforcement of tooth structure. The indications for the use of lithium disilicate are not limited to multiple facets of teeth in cases where there was no favorable response to tooth whitening, and also comprehend teeth with multiple restorations, diastema closure, shape alteration, and dental contouring, replacement of missing or fractured teeth, among others. The versatility of lithium disilicate ceramics allows its utilization in several clinical situations. The concomitant use of lithium disilicate for veneers and over metal has satisfactory aesthetic results, as reported in the present studying cases that require both aesthetics and resistance.

O restabelecimento da harmonia do sorriso através das cerâmicas odontológicas, quando realizado com critério e dentro de indicações específicas, traz resultados extremamente previsíveis. Para a reabilitação funcional e estética, muitos materiais cerâmicos podem ser empregados, como zircônia, leucita, alumina, feldspato e dissilicato de lítio. Dentre esses materiais, destaca-se o dissilicato de lítio que tem como características: resistência ao desgaste, ao ataque químico, à oxidação e a altas temperaturas; baixa condutividade elétrica; dilatação térmica próxima do zero; boas propriedades ópticas e biocompatibilidade com o periodonto; excelente estética; estabilidade de cor e reforço da estrutura dental. As indicações para o uso do dissilicato de lítio são múltiplas e não limitadas para facetas em casos de dentes onde não houve resposta favorável ao clareamento dental, dentes com restaurações múltiplas, fechamento de diastemas, alteração de forma e contorno dental, restituição de dentes ausentes ou fraturados, entre outras. A versatilidade da cerâmica de dissilicato de lítio faz com que possa ser utilizado em diferentes situações clínicas. Seu uso concomitante tanto para facetas como sobre núcleos metálicos fundidos é apresentado aqui com um resultado estético bastante satisfatório, sendo indicado para situações onde há necessidade de aliarmos estética e resistência como atributos indispensáveis.
Aesthetic rehabilitation of the smile using lithium disilicate ceramic system: clinical report
Keywords: Ceramics; Aesthetics; Dental veneers; Cerâmica; Estética; Facetas dentárias